Current status of the brown trout (Salmo trutta) populations within eastern Pyrenees genetic refuges1. Issue 1 (26th October 2015) - Araguas, Rosa M.; Vera, Manuel; Aparicio, Enric; Sanz, Nuria; Fernández‐Cebrián, Raquel; Marchante, Concha; García‐Marín, José L.
Abstract: Since the end of the 20th century, some headwaters of rivers in the eastern Pyrenees have been designated as genetic refuges to protect remaining native brown trout ( Salmo trutta ) diversity. The declaration was based on limited or no evidence of genetic impact from released non‐native Atlantic hatchery fish. Hatchery releases were completely banned into the genetic refuges, but pre‐existing fishing activities were maintained. Specific locations in each refuge have been monitored every 2–3 trout generations to update genetic information to accurately assess the contribution of these reservoirs to the preservation of native brown trout gene pools. This work updates genetic information to year 2014 in three of these locations (in Ter, Freser and Flamisell rivers). Previous studies identified hatchery introgressed populations within refuges and suggested discrepancies between the underlying intention of the genetic refuges and the gene pools detected. Therefore, we also examined genetic divergences among locations inside refuge river segments. Combined information at five microsatellite and the lactate dehydrogenase C ( LDH‐C* ) loci showed reduced but significant temporal native allele frequency fluctuations in some of the above specific locations that did not modify overall levels of local diversity and river divergences. Bayesian clustering analyses confirmed the presence of differentiated native units within each genetic refuge. Some locations of the Freser River within the genetic refuge area showed high hatchery impact of non‐native fish (over 20%). We discuss additional local actions (releases of native fish, selective removals and fishery reinforcement with sterile individuals) to improve the conservation objective of genetic refuges.